16.9k views
2 votes
What is te factorization of the expression below 9x^2-4y^2

User Nubela
by
5.2k points

1 Answer

2 votes

The factorization of the expression
9 x^(2)-4 y^(2) is (3x+2y) (3x-2y).

Solution:

In the expression
9 x^(2)-4 y^(2), 9 x^(2) can be written as
(3 x)^(2) . Similarly
4 y^(2) can be written as
(2 y)^(2)


9 x^(2)-4 y^(2)=(3 x)^(2)-(2 y)^(2)

Since both terms
(3 x)^(2) and
(2 y)^(2) are perfect squares, using the difference of squares formula,


a^(2)-b^(2)=(a+b)(a-b)

Here a = (3x) and b = (2y)


(3 x)^(2)-(2 y)^(2)=(3 x+2 y)(3 x-2 y)

(3x+2y) and (3x-2y) are the factors of
9 x^(2)-4 y^(2)

User Nullspace
by
5.1k points